Development of the â€œBisik Lalongklekâ€ Game to Improve Receptive Language Skills in Children Aged 4â€“5 Years - Rochmatul Alim; Rachma Hasibuan; Dewi Komalasari; Dwi Jayanti Kurnia Dewi (Ceria: Jurnal Program Studi Pendidikan Anak Usia Dini, 2025)
This study aims to develop a learning medium in the form of the â€œBisik Lalongklekâ€ game to enhance the receptive language skills of children aged 4â€“5 years. Receptive language ability is crucial for young children to understand instructions, recognize vocabulary, and provide appropriate responses. This study employed a Research and Development (R&D) method, involving stages of problem identification, product design, expert validation, product revision, and both limited and extensive trials. The research subjects were group A children aged 4â€“5 years, with data collected through observation and documentation. Validation results from material and media experts indicated that the â€œBisik Lalongklekâ€ game falls within the â€œhighly feasibleâ€ category, with an average feasibility percentage above 85%. The findings revealed that the children showed improvement in understanding instructions, recognizing vocabulary, and responding appropriately. This study demonstrates that integrating physical movement and traditional games can create enjoyable and meaningful learning experiences. The motor involvement and verbal interaction embedded in the game encourage children to be more active in processing information. Therefore, the â€œBisik Lalongklekâ€ game can serve as an innovative, educational learning medium aligned with the developmental characteristics of early childhood and can be effectively implemented by teachers in classroom learning activities.